Early Extracellular ATP Signaling in Arabidopsis Root Epidermis: A Multi-Conductance Process - Wang, Limin; Stacey, Gary; Leblanc-Fournier, Nathalie; Legué, Valérie; Moulia, Bruno; Davies, Julia M. (Frontiers in Plant Science, 2019)
ATP is an important extracellular signalling agent, operating in growth regulation, stomatal conductance and wound response. With the first receptor for extracellular ATP now identified in plants (P2K1/DORN1) and a plasma membrane NADPH oxidase revealed as its target, the search continues for the components of the signalling cascades they command. The Arabidopsis root elongation zone epidermal plasma membrane has recently been shown to contain cation transport pathways (channel conductances) that operate downstream of P2K1 and could contribute to eATP signalling. Here, patch clamp electrophysiology has been used to delineate two further conductances from root elongation zone epidermal plasma membrane that respond to eATP, including one that would permit chloride transport. This perspective addresses how these conductances compare to those previously characterized in roots and how they might operate together to enable early events in eATP signalling, including elevation of cytosolic free calcium as a second messenger. The role of the reactive oxygen species (ROS) that could arise from eATP’s activation of NADPH oxidases is considered in a qualitative model that also considers the regulation of plasma membrane potential by the concerted action of the various cation and anion conductances. The molecular identities of the channel conductances in eATP signalling remain enigmatic, but may yet be found in the multi-gene families of glutamate receptor-like channels, cyclic nucleotide-gated channels, annexins and aluminium-activated malate transporters.